Preliminary Study of S-Wave Velocity and Unconfined Compressive Strength of Cement- Palf Stabilised Kaolin - Chan, Chee Ming; Ch'ng, S.S. (International Journal of Integrated Engineering, 2011)
Clays are notoriously well known for giving rise to myriad problems and difficulties in construction due to excessive settlement and limited strength. Hence, there is a need to pretreat the soils prior to construction, such as improving the engineering properties via the stabilisation technique, before additional load can be applied on it. In soil stabilisation, cement is commonly used as a stabilizing agent, to simultaneously increase the strength and stiffness of the originally weak, soft material. However cement is relatively expensive and potentially harmful to the environment when admixed with soils. The need for alternative stabilizing agents which could reduce the use of cement is therefore apparent. In this study, natural fibres were retrieved from pineapple leaves, an agricultural waste product typical of Johor. Next pre-determined quantities of pineapple leaf fibres (PALF) were added to an artificial clay, kaolin, together with cement. The mixture was formed into specimens of 38 mm diameter and 76 mm high, cured in dry condition before being subjected to the s-wave velocity and unconfined strength measurements. A range of curing period was introduced to examine the effect of time on the performance of the stabilised specimens too. It was found that the fibres function as a form of reinforcement to the soil. Also, the test data revealed that PALF alone makes negligible contribution to the improved properties, where cement is necessary to act as a binder to strengthen the soil matrix. Nevertheless the potential of using PALF as an additive to cement in soft soil stabilisation is promising, though further work is necessary to better understand the stabilised material and its long term performance.